The Role of Platelets in Cardiovascular Disease: Molecular Mechanisms - Papapanagiotou, Angeliki; Daskalakis, Georgios; Siasos, Gerasimos; Gargalionis, Antonios; G. Papavassiliou, Athanasios (Current Pharmaceutical Design, 2016)
The role of platelets in atherosclerotic process and subsequently in the pathophysiology of cardiovascular disease is essential as platelets in addition to their contribution to thrombosis and hemostasis modulating inflammatory reactions and immune response. Platelets after adhesion on the injured vascular endothelium and activation release a wide range of molecules stored in platelets granules such as chemokines, proinflammatory molecules and other biological response modulators accelerating interaction among platelets, endothelial cells and leukocytes. These interactions establish a localized inflammatory response that promotes the atherosclerotic process. Moreover, activated platelets give rise to microparticles another active participant within the blood stream. The purpose of this review is to present the role of platelets in the above mechanisms giving an emphasis on the nature of the platelet derived- molecules and their contribution to the atherosclerotic process.
Keywords: atherosclerosis